PERILAKU MENYIMPANG PADA PEKERJAAN KARYAWAN HOTEL (Studi kasus pada karyawan House keeping SC Hotel dijalan Tuanku Tambusai) - Daniel Merdeka; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aimed to describe the factors which make deviatebehaviorism on hotel’s employee. The Method used in this research is qualitativeresearch which analized descriptively. The theory used in this research are theoryof Robert K.Merton with the tipology of adaptation ways on deviate behaviorism,theory of anomie and theory of Differential Association. In this research there are7 subjects, the techniques of collecting data are observation,interview anddocumentation.The result of this research shows that the deviate behaviorism at the hotel’semployee caused by less control from the management and the wrong procedureswhich done by the hotel’s guests such as; the of alcoholic and free seks. The twofactors which have big effed to make the employee do the deviate behaviorism areinternal factor and eksternal factor. Such as; environment,manager and thehotel’s guest and economic problem is also include which make the employee dothe deviate behaviorism.Keywords : Deviate behaviorism, Employee, Hotel